Orthostatic hypotension in diabetic patients-10-year follow-up study - Gaspar, Ludovit; Kruzliak, Peter; Komornikova, Andrea; Celecova, Zuzana; Krahulec, Boris; Balaz, David; Sabaka, Peter; Caprnda, Martin; Kucera, Marek; Rodrigo, Luis; Uehara, Yoshio; Dukat, Andrej (Journal of diabetes and its complications, 2016)
INTRODUCTION: Cardiovascular autonomic neuropathy in diabetics is a common but often underestimated and underdiagnosed complication of diabetes mellitus. One of the most clinical apparent forms of cardiovascular autonomic neuropathy is orthostatic hypotension. OBJECTIVES: To retrospectively assess the association of the orthostatic hypotension (OH) with macrovascular and microvascular complications of diabetes mellitus and to determine its effect on mortality. DESIGN AND METHODS: We retrospectively analyzed 187 patients with diabetes mellitus (60 patients with diabetes type 1 and 127 patients with diabetes type 2). Patients were divided into groups according to presence or absence of OH and type of diabetes. Association of OH with macrovascular and microvascular complications was evaluated and the effect of OH on 10-year all-cause mortality was also assessed. RESULTS: OH was present in 31.7% of patients with diabetes type 1 (DM1) and in 32.3% of patients with diabetes type 2 (DM2). OH was positively associated with the prevalence of myocardial infarction in DM1 (OR=10.67) and with prevalence of stroke in DM2 (OR=3.33). There was also a strong association of OH and the prevalence of peripheral artery disease in both DM1 (OR=14.18) and DM2 (OR=3.26). Patients with both types of diabetes and OH had significantly higher prevalence of nephropathy (DM1 OR=8.68, DM2 OR=3.24), retinopathy (DM1 OR=8.09, DM2 OR=4.08) and peripheral neuropathy (DM1 OR=17.14, DM2 OR=7.51) Overall 10year mortality rate was higher in diabetic patients with OH. CONCLUSIONS: Presence of OH in diabetics is associated with higher prevalence of macrovascular and microvascular complications of diabetes mellitus and also with higher 10-year mortality.
Keywords: Cohort Studies; Hypotension, Orthostatic; ambulantní kliniky nemocniční; Retrospective Studies; Diabetic Neuropathies; Hospitals, University; retrospektivní studie; Diabetic Nephropathies; Diabetic Angiopathies; Humans; Slovenská republika; diabetes mellitus 1. typu; Microvascular and macrovascular complications; Diabetes Mellitus, Type 1; kohortové studie; diabetické neuropatie; následné studie; lidé; Follow-Up Studies; ortostatická hypotenze; Diabetic Cardiomyopathies; lidé středního věku; Middle Aged; Orthostatic hypotension; stupeň závažnosti nemoci; nemocnice univerzitní; renální insuficience; Mortality; Outpatient Clinics, Hospital; Prevalence; kardiovaskulární nemoci; rizikové faktory; Diabetic cardiovascular autonomic neuropathy; Diabetes Mellitus, Type 2; Renal Insufficiency; Severity of Illness Index; diabetická kardiomyopatie; mortalita; diabetické nefropatie; Slovakia; Risk Factors; dospělí; Adult; diabetes mellitus 2. typu; prevalence; Diabetes mellitus; Cardiovascular Diseases; diabetické angiopatie